Land in Limbo: Understanding Planning Agencies and Spatial Development at the Interface of the Port and City of Naples - De Martino, Paolo (International Planning History Society Proceedings, 2016)
Numerous actors have been involved in the planning of the port and city of Naples; actors who have different ideas and goals, different tools, and even time-frames. The European Union, the Italian nation, the Campania Region, the Municipality of Naples, and the Port Authority act upon the port at different levels of planning. Each entity has different spatialities and temporalities. Their diverse goals have led port and city to develop into separate entities, from a spatial, functional as well as administrative point of view. The different scopes of their planning are particularly visible in the zone between port and city. Using and challenging the theory of path dependency, this paper explores the diverging ways in which a range of different institutions have planned for port and city starting from nineteenth century until today. It studies how the introduction of different institutions and their evolution has influenced plan making over time. The case of Naples shows the challenges that arise from the palimpsest of plans and goals associated with port and city, and that are particularly visible in the port-city interface in Naples.